Analysis of organophosphorus pesticides in vegetable samples by hollow fiber liquid phase microextraction coupled with gas chromatography-electron capture detection. - Sanagi, Mohd. Marsin (Taylor and Francis Ltd., 2010)
A method based on hollow fibre liquid phase microextraction (HF-LPME) coupled with gas chromatography electron capture detection (GC-ECD) has been developed for the determination of organophosphorus pesticides (OPPs) (chlorpyrifos and profenofos) in vegetable samples. In this method, a microsyringe needle with 1.5 cm polypropylene hollow fibre containing a volume of organic acceptor phase (n-dodecane) was immersed in an aqueous donor solution, and at the completion of extraction, the acceptor phase was withdrawn and transferred to GC-ECD for analysis. The effects of extraction solvent, volume of acceptor phase, and volume of donor phase were investigated. The optimized conditions for HF-LPME of the selected OPPs were n-dodecane as organic solvent, 11 mL of donor phase, and 3 µL of acceptor phase. The correlation coefficient (r2) of the calibration curves ranged from 0.998 to 0.999. The limits of detection (LOD) were between 0.099 and 0.128 µg/mL. The developed method provided excellent RSDs ranging from 0.54% to 8.00% and analyte recoveries ranging from 60.8% to 88.0%. This method was applied successfully for determination of organophosphorus pesticides in selected vegetables.